Assessment of regional influence from a petrochemical complex by modeling and fingerprint analysis of volatile organic compounds (VOCs). (September 2016) - Su, Yuan-Chang; Chen, Sheng-Po; Tong, Yu-Huei; Fan, Chen-Lun; Chen, Wei-Hao; Wang, Jia-Lin; Chang, Julius S.
Abstract: This study aimed to demonstrate a strategy to investigate the influence of volatile organic compounds (VOCs) on its neighboring districts from a gigantic petrochemical complex. Monitoring of the VOCs in the region was achieved by a nine-station network, dubbed photochemical assessment measurement stations (PAMS), which produced speciated mixing ratios of 54 non-methane hydrocarbons (NMHCs) to represent VOCs with an hourly resolution within a 20 km radius. One-year (2013/10/1–2014/9/30) worth of PAMS data from the network were used in forms of total NMHCs (called PAMS-TNMHC) and speciated mixing ratios. Three dimensional modeling coupled with PAMS measurements successfully elucidated how the study domain was affected by the petrochemical complex and distant sources under three typical seasonal wind patterns: northeast monsoonal, southwest monsoonal, and local-circulation. More exquisite analysis of influence on the neighboring districts was permitted with the use of speciated mixing ratios of VOCs provided by the PAMS network. The ratios of ethylene/acetylene (E/A) > 3 and propylene/acetylene (P/A) > 1.5 were used as indicators to reveal the PAMS sites affected by the petrochemical emissions. Consequently, the hourly speciated data from the nine PAMS sites enabled a finer assessment of the districts affected by the complex to calculate the percent time of influence (dubbed TI%) for all the sites (districts). It was found that the region was more affected by the complex under both the northeast monsoonal and the local-circulation wind types with some of the PAMS sites greater than 5% for the TI%. By contrast, influence on the region was found minimal under the southwest monsoonal flow with the TI% small than 1.5% across all sites. This study successfully devised a method of assessment with the use of speciated measurements of selected VOCs and modeling to assess the influence of a prominent source on the neighboring districts by filtering out irrelevant sources under the complex meteorological conditions. Highlights: Exploiting a gigantic petrochemical complex as a prominent VOCs source. Regional influence was assessed by a VOCs network and model simulations. VOCs fingerprints in ratios were used to indicate petrochemical influence. The percent time of influence at 8 VOCs sites was quantified using hourly VOCs data.